Abnormal T cell differentiation persists in patients with rheumatoid arthritis in clinical remission and predicts relapse. Issue 6 (20th July 2007) - Burgoyne, C H; Field, S L; Brown, A K; Hensor, E M; English, A; Bingham, S L; Verburg, R; Fearon, U; Lawson, C A; Hamlin, P J; Straszynski, L; Veale, D; et al.
Abstract : Objectives: An abnormal CD4+ T cell subset related to inflammation exposure (inflammation-related cells, IRC) has been identified in rheumatoid arthritis (RA). Patients with inflammatory and non-inflammatory diseases were used to examine the relationship between inflammation and this T cell subset in vivo. Methods: Blood was collected from healthy controls and patients with RA (active disease or in clinical remission), Crohn's disease and osteoarthritis. IRC and chemokine receptors were quantified by flow cytometry. Thymic activity and apoptotic factors were measured by real-time polymerase chain reaction. Circulating cytokines were measured by enzyme-linked immunosorbent assay. CXCR4 and SDF1 in synovial biopsies were measured using immunohistochemistry. Results: IRC were identified in patients with RA (p<0.0001) and Crohn's disease (p = 0.005), but not in those with osteoarthritis. In RA in remission, IRC persisted (p<0.001). In remission, hyperproliferation of IRC was lost, chemokine receptor expression was significantly lowered (p<0.007), Bax expression dropped significantly (p<0.001) and was inversely correlated with IRC (rho = −0.755, p = 0.03). High IRC frequency in remission was associated with relapse within 18 months (OR = 6.4, p<0.001) and a regression model predicted 72% of relapse. Conclusions: These results suggest a model in which, despite the lack of systemic inflammation, IRC persist in remission, indicating that IRC are an acquired feature of RA. They have, however, lost their hyper-responsiveness, acquired a potential for survival, and no longer express chemokine receptors. IRC persistence in remission confirms their important role in chronic inflammation as circulating precursors of pathogenic cells. This was further demonstrated by much higher incidence of relapse in patients with high IRC frequency in remission.